Fronteiras de um universo insólito : as identidades híbridas em A varanda do frangipani - Lacourt, Gisela (2014)
The novel A varanda do frangipani, by Mia Couto, had its first edition published in 1996 by Editora Caminho of Portugal. It is a narrative heavily permeated by the unusual phenomenology, where the marvelous and fantastic dispute for their limits. A ghost narrator tells the story of a police investigator and a group of elderly people living alone in an old Portuguese fortress. The author creates in this work a universe of hybrid crossbreed borders and identities. This study, therefore, investigates the relationship of the fictional unusual with Mozambican cultural identity, constituting a survey of bibliographic nature. The assumptions underlying this study are the ideas of the scholar Stuart Hall on cultural identity in postmodernity, the theoretical considerations of Homi Bhabha about the cultural hybridity, the notion of Orientalism in Edward Said 's theory the thoughts of Tzvetan Todorov about the construction of fantastic literature, the studies of Portuguese critic Filipe Furtado about the construction of the fantastic in the narrative as well as the contributions of Brazilian researchers Bella Josef, Irlemar Chiampi, Flavio Garcia and Jane Tutikian